Bank credit and trade credit after the financial crisis: evidence from rural Galicia - Peón, David; Guntín, Xulia (Journal of Business Economics and Management, 2021)
Access to external finance is a key challenge for the creation, survival and growth of SMEs. This article delves into the “weak funding” handicap of rural small firms (SEs): the access to bank financing and the substitutive role of trade credit for entrepreneurs in rural areas when they faced bank credit constraints. Considering SEs in Galicia (Spain), a paradigmatic case in Europe of rural areas in demographic decline with a strong impact of the Spanish sovereign and banking crisis of 2008–2012. There’s evidence of firms in rural areas facing a differential negative flow of bank credit during the financial crisis, especially in the manufacturing and construction sectors, that dissipated afterwards. Then, using a panel data approach that considers the determinants of trade credit, the complementary and substitutive hypotheses are tested to estimate the impact of bank credit restrictions over trade credit.